Hedge Expression on The Novel of ABC Murder by Agatha Christie in Two Decades Versions - Ilham Ilham; Bulkani Bulkani; Saiffullah Darlan (ETERNAL (English Teaching Journal), 2016)
Everything changes, no exception with how the way to communicate, language through the times. In communication among the times, we found the phenomena which related to language barriers, i.e. the difference of cross-culture, race, ethnicity, gender, customs. Furthermore, based on the phenomenon above, it becomes very interesting to explore languages and cultures especially in hedge expression in literary text from the novel of ABC Murder written by Agatha Christie and it’s two decade of translation versions, 1976 and 2017. This study is aim to find the function and form of hedge and the translation technique among two translation versions. This study used qualitative research method with the data collection technique by using purposive sampling. Moreover, the collected data are analyzed and classified to see the translation technique used. Additionally, interpretation of the data will have discussed in this paper. Translation technique proposed by Molina & Albir used to see the technique used by translator. The results of the study show that, hedge expression gave an impact in our speech act, especially in politeness context. Moreover, the deletion or the shifting of hedge can change our utterance in cooperative principle context.